Sustainable consumption and the comprehensive economic well-being of American households - Daniel Cooper; Barry Z. Cynamon; Steven M. Fazzari (Federal Reserve Bank of Boston, 2023)
This paper develops a comprehensive measure of household economic well-being. The "sustainable consumption" concept accounts for income, assets, debt, transfer payments, and asset returns to estimate a consumption path that balances resources with expenditure over a household's lifetime. Calculating sustainable consumption using Panel Study of Income Dynamics data demonstrates that it acts as an anchor for actual household spending. Results show that following a period of rapid growth from the mid-1980s to the early 2000s, sustainable consumption stagnated on average. In the aftermath of the Great Recession, the decline in sustainable consumption exceeded the fall in actual consumption due in part to a decline in real asset returns. Decomposing sustainable consumption reveals the relative importance of different household resources in determining well-being and how these factors evolve over time - insights that would be missed when resources such as income or wealth are considered separately. Taxable income supports the majority of sustainable consumption; however, as a share of households' lifetime resources, taxable income has decreased on average while the Social Security share has grown.
Keywords: E21; I31; 330; household spending; sustainable consumption; economic well-being